Constraints in the Implementation of Electronic Medical Records at Puskesmas in accordance with Permenkes 24 of 2022 - Anastasia Ratnawati; Dwi Iskandar (Universitas Muhammadiyah Malang, 2025)
The implementation of electronic medical records (EMR) in health centers is an important step to improve the quality of health services in Indonesia, which is regulated by the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022. Despite this, most health centers in Indonesia still face obstacles in implementing this system. This study aims to analyze the various obstacles faced by Puskesmas in implementing electronic medical records through a literature study approach. The methodology used included article exploration and selection of relevant articles based on certain inclusion criteria. The analysis showed that the main obstacles include human resources, hardware and software infrastructure, network, funding, and the absence of standard operating procedures (SOPs). The findings are expected to serve as a basis for the government and puskesmas in formulating effective policies to overcome the challenges in implementing electronic medical records in puskesmas.